2001
DOI: 10.1016/s0014-5793(01)02292-x
|View full text |Cite
|
Sign up to set email alerts
|

NaCl‐activated nucleoside diphosphate kinase from extremely halophilic archaeon, Halobacterium salinarum, maintains native conformation without salt

Abstract: Enzymes from extremely halophilic archaea are readily denatured in the absence of a high salt concentration. However, we have observed here that a nucleoside diphosphate kinase prepared from Halobacterium salinarum was active and stable in the absence of salt, though it has the amino acid composition characteristic of halophilic enzymes. Recombinant nucleoside diphosphate kinase expressed in Escherichia coli requires salt for activation in vitro, but once it acquires the proper folding, it no longer requires t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 22 publications
3
63
0
Order By: Relevance
“…In contrast, HsNDK from H. salinarum was active and stable in the low-salt conditions, as we have reported previously [6]. Here we demonstrated that HsNDK associates into a hexamer at 3.8 M NaCl and dissociates into a dimer at 0.2 M NaCl reversibly depending on the salt concentrations without converting into enzymatically inactive monomer.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In contrast, HsNDK from H. salinarum was active and stable in the low-salt conditions, as we have reported previously [6]. Here we demonstrated that HsNDK associates into a hexamer at 3.8 M NaCl and dissociates into a dimer at 0.2 M NaCl reversibly depending on the salt concentrations without converting into enzymatically inactive monomer.…”
Section: Discussionsupporting
confidence: 80%
“…Since HsNDK is enzymatically active in 0.2 M NaCl [6], we ¢rst examined the secondary structure of HsNDK in both high-and low-salt conditions. The far UV CD spectrum of HsNDK in 3.8 M NaCl showed a secondary structure containing 29% K-helix, 19% L-sheet and 18% L-turns (Fig.…”
Section: Secondary Structures Of Hsndk At High-and Low-salt Concentramentioning
confidence: 99%
“…DnaK itself has MW of 67.4 kDa, from which its alias Hsp 70 was historically coined, but is predicted to migrate as 88.9 kDa in gels. A western blot performed seventeen years ago to study a nucleoside diphosphate kinase [67] also shows a clear ~45 kDa band with the same expression patterns of the DnaK band [68] (Fig. S18).…”
Section: Resultsmentioning
confidence: 99%
“…The refolded sample was incubated overnight at 4°C and measured for enzyme activity. Enzymatic activity was assayed as described before [4], except for using a micro-titer plate (the volume of reaction mixture was 0.2 ml) and a plate reader (Benchmark Plus, Bio-Rad). The HsNDK mutant gene of interest thus isolated was re-cloned at NdeI/BamHI site of pET3a to construct pG114R, analyzed by ABI PRISM 3100 Genetic Analyzer (Applied Biosystems) for DNA sequence determination, and used for further characterization.…”
Section: Isolation Expression and Screening Of Hsndk Mutantsmentioning
confidence: 99%